Are calcifying microvesicles another analogous substructure of calcifying nanoparticles? - Atughonu TC (Dove Medical Press, 2013)
Trueman C Atughonu, Sateesh B Arja, Farooq A ShiekhAvalon University School of Medicine, Willemstad, CuracaoWe correspond in response to the article entitled, "Contrast-enhanced MR imaging of atherosclerosis using citrate-coated superparamagnetic iron oxide nanoparticles: calcifying microvesicles as imaging target for plaque characterization" by Wagner et al.1 In this article, the authors have used a new term "calcifying microvesicles" for the first time in the literature. We think our commentary will highlight these calcifying microvesicles with the similar analogous structures already existing in nature. We hope our discussion will clear up many of those questions.View original paper by Wagner and colleagues.